2001
DOI: 10.1007/s004310100834
|View full text |Cite
|
Sign up to set email alerts
|

Correction of length discrepancies and angular deformities of the leg by Blount's epiphyseal stapling

Abstract: Blount's epiphyseal stapling can be recommended as a safe procedure with predictably good results in idiopathic angular deformities of the leg and leg length difference caused by overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 21 publications
(38 reference statements)
4
70
1
8
Order By: Relevance
“…Staple epiphyseodesis is usually performed well before the anticipated physiological termination of growth and not recommended for children younger than ten years. Raab et al observed in their study of 34 extremities treated with Blount staples a higher rate of loosening and displacement of the staples in children younger than eight years, which was statistically significant [14]. In contrast to this observation, however, Mielke and Stevens noted only one case of staple loosening on their study sample of 25 patients who underwent surgery at an average age of 6.3 years [9].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Staple epiphyseodesis is usually performed well before the anticipated physiological termination of growth and not recommended for children younger than ten years. Raab et al observed in their study of 34 extremities treated with Blount staples a higher rate of loosening and displacement of the staples in children younger than eight years, which was statistically significant [14]. In contrast to this observation, however, Mielke and Stevens noted only one case of staple loosening on their study sample of 25 patients who underwent surgery at an average age of 6.3 years [9].…”
Section: Discussionmentioning
confidence: 82%
“…Another aspect to be aware of is the rebound effect after implant removal which is why slight overcorrection should be achieved [14,17,18]. This effect is also postulated for the 8-plate, even if no data exist in the current literature confirming this theory.…”
Section: Discussionmentioning
confidence: 99%
“…P. Raab [45] опублікував результати лікування Рисунок 3. Фотовідбиток рентгенограми двобічного блокування проксимальної НЗ великогомілкової кістки за допомогою скоб Блаунта 48 дітей, які свідчать про безпеку та високу ефектив-ність використання скоб Блаунта при корекції РДНК, особливо в дітей з гемігіпертрофічними синдромами.…”
Section: рисунок 1 техніка відкритого епіфізеодезу за Phemister рисуunclassified
“…La epifisiodesis generalmente se indica en la dismetría por predicción al momento de la madurez de 2-5 cm., en niños con un crecimiento remanente suficiente como para corregirla (6) (8) (9)(10)(11) (12) . Dismetrías de menos de 2 cm.…”
Section: )(8)unclassified